2019
DOI: 10.1039/c9nr02019e
|View full text |Cite
|
Sign up to set email alerts
|

Highly concentrated and stabilizer-free transition-metal dichalcogenide dispersions in low-boiling point solvent for flexible electronics

Abstract: Liquid-phase exfoliation of TMDCs was studied in a low-boiling point solvent, and the highest concentration of dispersions without surfactants was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…Hansen matching (smaller interaction radius) and higher viscosity 41 . Chemical characterisation (XPS) and microscopy (HRTEM and AFM micrographs) in that work 40 does not indicate the presence of molybdenum oxides. It is observed that the zeta potential for nanosheets exfoliated in acetone is significantly higher than for those reported in 2-butanone.…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…Hansen matching (smaller interaction radius) and higher viscosity 41 . Chemical characterisation (XPS) and microscopy (HRTEM and AFM micrographs) in that work 40 does not indicate the presence of molybdenum oxides. It is observed that the zeta potential for nanosheets exfoliated in acetone is significantly higher than for those reported in 2-butanone.…”
Section: Methodsmentioning
confidence: 80%
“…Hansen parameters for 2-butanone 7 , a linear ketone containing one extra carbon than acetone, are 16.0, 9.0 and 5.1 MPa 1/2 , for dispersive, polar and hydrogen bonding components, respectively. Highly concentrated dispersions of TMDs in 2-butanone using bath sonication was obtained by Lobo et al 40 . A similar degree of exfoliation was obtained by them, as indicated by peak separation of the in-plane and out-of-plane Raman modes for MoS2 (24.2 cm -1 for acetone and 24.9 cm -1 for 2-butanone).…”
Section: Methodsmentioning
confidence: 99%
“…It has been theoretically reported that apart from the matching of HSP values, factors such as the structure of the solvent, its bulkiness and its re-orientation on the exfoliated nanosheets are other critical parameters to be considered for efficient exfoliation [15,16]. These theoretical studies were also supplemented with experimental observations where it was demonstrated that the simple addition of a -CH 2 group to a solvent drastically changes the efficiency of the LPE process [17][18][19]. It is also reported that the exfoliation efficiency of layered materials may differ depending on the bulk precursor.…”
Section: Resultsmentioning
confidence: 99%
“…[183,184] Many researchers focused on using additives and surfactants in water and low-boiling solvents to stabilize nanosheets. [185][186][187][188] As long as it is able to match the surface tensions of both the liquid phase and the nanosheet faces within the solid-liquid interface to promote colloidal dispersion, the surfactant type does not appear to be excessively important. [181,189] Growth of surfactant aided exfoliation has to gain lots of attention as a broad exploration of an assortment of surfactants which serves as additives for the stabilization or equilibrium of nanosheets.…”
Section: Dynamics Of Liquid-phase Exfoliationmentioning
confidence: 99%